Korea - Richmond, Simon; Eaves, Megan;Holden, Trent;Milner, Rebecca;Tang, Phillip;Whyte, Rob (Footscray, Victoria : Lonely Planet Publications, 2016)
This book is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Walk along Cheong-gye-cheon's long-buried stream, hike around Jeju-do's volcanic landscape, or jump into a vat of mud during the Boryeong Mud Festival; all with your trusted travel companion. Get to the heart of Korea and begin your journey now!
Seoul -- Around Seoul -- Gangwon-do -- Gyeongsangbuk-do -- Busan & Gyeongsangnam-do -- Jeollanam-do -- Jeju-do -- Jeollabuk-do -- Chungcheongnam-do -- Chungcheongbuk-do -- North Korea.
Includes index.
Keywords: GUIDEBOOKS